Modelo multicritério para classificação e priorização de itens em apoio à gestão do portfólio de produtos - Silva, Thais da (2020)
Product portfolio management, in recent years, is increasingly present in organizations as an alternative to enable changes and to improve control over their processes, providing a detailed view of the strategies that should guide the balance of the product portfolio and to allow an appropriate allocation of the products. The diversity of products that make up a portfolio induces organizations to seek practical support for methods that assist in decision making.The decision-making process concerningthe portfolio converges with the focus of the multicriteria decision since these decisions ofteninvolve severalconflicting criteria. Thus, the present study aimedto develop a multicriteria classificationand prioritizationmodel, serving asa guide to decisions related to the product portfoliomanagement. For this, the methodological procedures were guided through literature reviews in order to identify methods, tools and criteria most used in the context of portfolio management supportingthe construction of the model.The model proposed in the study used the approach based on the multicriteria decision support method, ELECTRE TRI, for the classification of products. The model also had the support of IRIS version 2.0 software to emulate the results of the preferences dictated by the decision-maker and the AHP to define the criteria weights.Through the results,it was verified the applicability and stability of the model, which allowed classification of the products intothree classes: candidate products to exclude (1), derivative products (2),and products with priority (3). Four evaluation criteria were considered, defined as time to market(1),competitive advantage (2), strategic alignment (3)and contribution margin(4). After the construction of the model, an application was made in a company in the metal mechanic branch.Of the classified products froma set of 40 items, it was found that 47.5% were allocated to class(2)indicating a potential to undergo some type of incremental changes in the product or process. Concerningclasses(1)and (3)these obtained a similar percentage of allocated products, 27.5% and 25% consecutively, since, products of class(1), did not obtain a good performance regarding criterion (3), which had the highest weighting value. The products allocated to class (3)obtained had higher performance withcriteria2, 3and 4, followingthe company's strategies.However, the model allows the decision-maker a clearer strategic perspectiveto assist in decision making regarding the product portfolio, aiming at a balanced portfolio compatible with the company's strategies.